THE INFLUENCE OF INTERNAL AND EXTERNAL FACTORS ON THE PROFITABILITY OF STATE-OWNED BANKS IN INDONESIA FOR THE 2009-2019 PERIOD - Carissa Vania; Sri Yani Kusumastuti (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2022)
This research was conducted with the aim of estimating the influence of internal factors in the form of Capital Adequacy Ratio (CAR), Non-Performing Loan (NPL), Operating Costs/Operating Income (BOPO), and Loan to Deposit Ratio (LDR) as well as external factors in the form inflation, interest rate, exchange rate, and gross domestic product (GDP) on the profitability of BUMN banks in 2009-2019 using a measuring instrument in the form of Return on Asset (ROA). This study uses data obtained from the annual financial reports of each BUMN banks and from Bank Indonesia website. The data analysis technique used is panel data regression and hypothesis testing in the form of F test - Global dan t test – Parsial using a significance level of 5%. In addition, the Wald test was also carried out to see which independent variables could be eliminated in this study. The result shows that LDR has a positive effect on profitability. Meanwhile NPL, BOPO, and exchange rate have a negative effect on profitability.